Problem Ajaran Inkarnasi Mistis dalam Kristologi: Analisa Dogmatis dan Teologis - Manurung, Pangeran (Jurnal Teologi dan Pelayanan Kerusso, 2024)
This article discusses the understanding of mystical incarnation within the context of the Logos Seminar, a theological forum that often provides alternative perspectives on traditional doctrines. The main focus of the article is the differing interpretation of incarnation presented by the Logos Seminar compared to the traditional understanding of incarnation upheld by the Church. The Logos Seminar claims that the Church’s understanding of incarnation has been influenced by pagan culture, leading to a mystical interpretation of the concept. The aim of this study is to critically examine the mystical incarnation concept promoted by the Logos Seminar and to evaluate its theological claims in comparison to traditional doctrines and systematic theology scholars' views. Through dogmatic and theological analysis, the author explores the core ideas of mystical incarnation and compares them with the perspectives of systematic theology scholars. The findings reveal that the mystical incarnation concept contradicts two key aspects: (1) the theological meaning of "God coming into the world" as described in several letters of the New Testament, and (2) the approach proposed by mystical incarnation differs from previous scholars' approaches, who, despite their varying methods, consistently emphasized the divinity of Jesus during His ministry on earth. While John’s Gospel introduces the incarnation as part of the mission of salvation, the mystical incarnation views it as a human process, placing Jesus on par with ordinary humans, comparable to Adam.